2020
DOI: 10.1002/srin.201900662
|View full text |Cite
|
Sign up to set email alerts
|

Work Roll Shifting Strategy of Uneven “Cat Ear” Wear Control for Profile and Flatness of Electrical Steel in Schedule‐Free Rolling

Abstract: There are severe uneven “cat ear” wear contours of work rolls, the key factors to affect high‐quality profile and flatness control of electrical steel strips, in the schedule‐free rolling process with a large number of the same width strip rolling campaigns of hot rolling mills. The work roll wear prediction model, thermal roll contour model, and a 3D finite‐element model of roll stacks and strip are established using MATLAB and ABAQUS software. The effects of the work roll wear contour on the loaded roll gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Li et al [6] put forward a reverse continuously variable crown backup roll contour, and roll wear can be improved with this contour. Shang et al, [7,8] Cao et al, [9] Dong et al, [10] and Yamaguchi et al [11] developed work roll shifting strategies, thereby keeping work roll contour be effective in adjusting strip profile. In addition, high-wear resistance materials are adopted to produce work roll.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [6] put forward a reverse continuously variable crown backup roll contour, and roll wear can be improved with this contour. Shang et al, [7,8] Cao et al, [9] Dong et al, [10] and Yamaguchi et al [11] developed work roll shifting strategies, thereby keeping work roll contour be effective in adjusting strip profile. In addition, high-wear resistance materials are adopted to produce work roll.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al 18 analysed the effect of TWW on the crown of the LRGP in hot strip rolling using the influence function method, and discovered that when the wear crown is up to 0.2 mm, the control ability of the WR continuously variable crown (CVC) shifting on the LRGP will become ineffective. Cao et al 19 simulated and analysed the influence of the WR wear on the LRGP in different rolling stages in hot strip rolling, and found that the crown of the LRGP increases with the WR wear. Likewise, Pathak et al 20 found that the strip crown increases with roll wear in hot strip rolling via experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Abdulrahman et al [ 11 ] studied the influences of rolling process parameters such as the work roll cross angle and work roll shifting on the strip shape and profile of the thin strip. Cao et al [ 16 ] proposed a variable stroke and step (VSS) shifting strategy to reduce uneven “cat ear” wear contours of work rolls, and the industrial application of the VSS shifting strategy gives remarkable results.…”
Section: Introductionmentioning
confidence: 99%